STRANGE BARYON PRODUCTION IN E+ E- ANNIHILATION - Braunschweig, W; Gerhards, R; Kirschfink, F; Martyn, H; Bock, B; Fischer, H; Hartmann, H; Hartmann, J; Hilger, E; Jocksch, A; Wedemeyer, R; Foster, B; et al. (Springer-Verlag, 1989)
The production of strange baryons in e+e- annihilation has been studied at centre of mass energies of 34.8 GeV and 42.1 GeV, using the TASSO detector at DESY. Inclusive cross-sections have been obtained for Λ0 and Ξ- production and an upper limit has been placed upon the production rate of Σ*±(1385). We measure the Λ0 multiplicity per event to be Mathematical expression and Mathematical expression at Mathematical expression and 42.1 GeV respectively. The Ξ- multiplicity per event is found to be Mathematical expression at Mathematical expression. An investigation has been made of the extent to which Λ0 are produced in pairs. The Λ0 cross-section has been studied as a function of event sphericity. © 1989 Springer-Verlag.